2015
DOI: 10.5194/soil-1-411-2015
|View full text |Cite
|
Sign up to set email alerts
|

Predicting soil water repellency using hydrophobic organic compounds and their vegetation origin

Abstract: Abstract. It is widely accepted that soil water repellency (SWR) is mainly caused by plant-derived hydrophobic organic compounds in soils; such hydrophobic compounds are defined as SWR markers. However, the detailed influence of SWR markers on SWR is yet unclear and the knowledge of their original sources is still limited. The aims of this study are to select important SWR markers to predict SWR based on their correlation with SWR and to determine their origin. In our study, sandy soils with different SWR were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 60 publications
5
34
0
Order By: Relevance
“…It is defined as when water drop contact angles are between 0 and 90° (Buczko et al, 2006), or when repellency index (RI) values determined from sorptivity of ethanol and water are >1.95 (Hallett et al, 2001). Soil water repellency may be derived from above‐ and below‐ground vegetation; but more recent research has suggested that hydrophobic compounds from roots (especially grasses) may be more important than previously thought (Mao et al, 2014, 2015, 2016).…”
mentioning
confidence: 99%
“…It is defined as when water drop contact angles are between 0 and 90° (Buczko et al, 2006), or when repellency index (RI) values determined from sorptivity of ethanol and water are >1.95 (Hallett et al, 2001). Soil water repellency may be derived from above‐ and below‐ground vegetation; but more recent research has suggested that hydrophobic compounds from roots (especially grasses) may be more important than previously thought (Mao et al, 2014, 2015, 2016).…”
mentioning
confidence: 99%
“…Remarkable are the often huge spatial differences in persistence of actual water repellency in the grass-covered plots across a horizontal difference of 75 cm, with wettable as well as slightly, strongly, severely, and extremely water repellent soil samples. These differences in persistence may partly be due to differences in soil water content, but may also be the result of differences in hydrophobic compounds and their concentrations as found by Mao et al (2014Mao et al ( , 2015. Gordon and Hallett (2014) describe even the spatial variability of the severity of soil water repellency at the millimetre scale by means of the contact angle.…”
Section: Discussionmentioning
confidence: 99%
“…These substances may be released from a variety of plant species, decaying organic matter, soil fauna, and microorganisms (e.g. Mao et al, 2014Mao et al, , 2015MataixSolera et al, 2007). This coating does not necessarily cover the soil particles completely nor is it always very thick.…”
Section: Introductionmentioning
confidence: 99%
“…The highest severity of soil WR has been observed below conifers (firs, cedars and pines), whereas soils below oaks have been found to be much more wettable. These results are in agreement with findings from other authors, who have reported that conifers are much more prone than oaks to induce soil WR, because of the chemical composition of their tissues, which include resins, waxes and other substances able to cause hydrophobicity in soils (Conde et al ., ; Ito et al ., ; Mataix‐Solera & Doerr, ; Lozano et al ., ; Mao et al ., ). Different authors have reported soil WR in oaklands from Mediterranean areas (Cerdà et al ., ; Mataix‐Solera et al ., ; Jordán et al ., ; Zavala et al ., ; Zavala et al ., ).…”
Section: Discussionmentioning
confidence: 98%